Synthetic Biology Approaches for Improving Chemical Production in Cyanobacteria - Treece, Tanner R.; Gonzales, Jake N.; Pressley, Joseph R.; Atsumi, Shota (Frontiers in Bioengineering and Biotechnology, 2022)
Biological chemical production has gained traction in recent years as a promising renewable alternative to traditional petrochemical based synthesis. Of particular interest in the field of metabolic engineering are photosynthetic microorganisms capable of sequestering atmospheric carbon dioxide. CO2 levels have continued to rise at alarming rates leading to an increasingly uncertain climate. CO2 can be sequestered by engineered photosynthetic microorganisms and used for chemical production, representing a renewable production method for valuable chemical commodities such as biofuels, plastics, and food additives. The main challenges in using photosynthetic microorganisms for chemical production stem from the seemingly inherent limitations of carbon fixation and photosynthesis resulting in slower growth and lower average product titers compared to heterotrophic organisms. Recently, there has been an increase in research around improving photosynthetic microorganisms as renewable chemical production hosts. This review will discuss the various efforts to overcome the intrinsic inefficiencies of carbon fixation and photosynthesis, including rewiring carbon fixation and photosynthesis, investigating alternative carbon fixation pathways, installing sugar catabolism to supplement carbon fixation, investigating newly discovered fast growing photosynthetic species, and using new synthetic biology tools such as CRISPR to radically alter metabolism.